Seagulls and Beaches as Reservoirs for Multidrug-Resistant Escherichia coli - Roméo Rocha Simões; Laurent Poirel; Paulo Martins Da Costa; Patrice Nordmann (Emerging Infectious Diseases, 2010)
A variety of extended-spectrum β-lactamase–producing Escherichia coli isolates, with a high rate of cefotaximase-15 resistance, were identified in seagull feces from Porto, Portugal, beaches. Beaches may therefore present a risk to public health because of the potential pathogen-spreading capacity of migratory birds.